Avant-Garde, Art Deco, Eclecticism: PB Discussion Club - Bagina, Elena; Kapustin, Petr (project baikal, 2019)
Historians of architecture have not arrived at a common view on the processes occurring in architecture in the 1920–1930s. The genesis of such a phenomenon of the world architecture as Art Deco is of special interest.